Engaging Latina cancer survivors, their caregivers, and community partners in a randomized controlled trial: Nueva Vida intervention. - Rush, Christina L; Darling, Margaret; Elliott, Maria Gloria; Febus-Sampayo, Ivis; Kuo, Charlene; Muñoz, Juliana; Duron, Ysabel; Torres, Migdalia; Galván, Claudia Campos; Gonzalez, Florencia; Caicedo, Larisa; Nápoles, Anna; et al. (Quality of Life Research, 2015)
Introduction: Few studies have evaluated interventions to improve quality of life (QOL) for Latina breast cancer survivors and caregivers. Following best practices in community-based participatory research (CBPR), we established a multi-level partnership among Latina survivors, caregivers, community-based organizations (CBOs), clinicians, and researchers to evaluate a survivor-caregiver QOL intervention.Methods: A CBO in the mid-Atlantic region, Nueva Vida, developed a patient-caregiver program called Cuidando a mis Cuidadores (Caring for My Caregivers), to improve outcomes important to Latina cancer survivors and their families. Together with an academic partner, Nueva Vida and three CBOs established a multi-level team of researchers, clinicians, Latina cancer survivors, and caregivers to conduct a national randomized trial to compare the patient-caregiver program to usual care.Results: Incorporating team feedback and programmatic considerations, we adapted the prior patient-caregiver program into an 8-session patient- and caregiver-centered intervention that includes skill-building workshops such as managing stress, communication, self-care, social well-being, and impact of cancer on sexual intimacy. We will measure QOL domains with the patient-reported outcomes measurement information system, dyadic communication between the survivor and caregiver, and survivors' adherence to recommended cancer care. To integrate the intervention within each CBO, we conducted interactive training on the protection of human subjects, qualitative interviewing, and intervention delivery.Conclusion: The development and engagement process for our QOL intervention study is innovative because it is both informed by and directly impacts underserved Latina survivors and caregivers. The CBPR-based process demonstrates successful multi-level patient engagement through collaboration among researchers, clinicians, community partners, survivors, and caregivers.